Decentralization of Education Planning and Its Impact in Quality - Mainali, Bhawani Prasad (Academic Voices: A Multidisciplinary Journal, 2014)
This article has attempted to present an overview of basic concept, rationale and trends of decentralization in education planning and to identity the major policy issues and challenges relating to educational quality in Nepalese context. Decentralization in education around the world has based on the assumption that the quality of education will improve by shifting a decision making and accountability closer to schools, class rooms and learners. Academic Voices, Vol. 3, No. 1, 2013, Pages 4-12 DOI: http://dx.doi.org/10.3126/av.v3i1.9979